DETERMINANTS OF FIRM VALUE WITH FIRM SIZE AS MODERATING VARIABLE - Tanaya, Catherine Carissa; Wirianata, Henny (International Journal of Application on Economics and Business, 2025)
The fundamental purpose of a business is to enhance investor wealth, which is closely related to increasing market value. Especially in the consumer non-cyclical sector, companies try to maintain stability through the provision of essential goods that tend to be resistant to economic changes. This study intents to examine how profitability (ROE) and leverage (DER) impact a company's valuation (PBV), using the moderating role of company size. This research focused on companies in consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The purposive sampling method was chosen to use 33 companies, resulting in 132 samples in this study. The data were analysed using panel data regression and moderation regression analysis, with EViews 12 employed as the data processing tool. The proceeds demonstrate that both profitability and leverage exert a positive and substantial affect the business value. Additionally, enterprise scale does not moderate the connection between profitability and firms worth. However, it weakens the positive relation of leverage and company value. Hence, this suggests that company size may weaken the impression of leverage on the enterprise value, suggesting a signal to investors.